Development of a student assistance program - Desmond, Michael (My University, 1987)
This seminar paper presents the development of a Student Assistance Program at Aquinas High School, La Crosse, Wisconsin. The program was based upon a perceived need to help students develop both personally and spiritually. The goa1s of the program involve creating a support system to meet the specific needs of the individual student. Featured in this support system are in-school support groups whose primary function is to address the issue of self-esteem.
Keywords: Aquinas High School (La Crosse, Wis.); High school students -- Wisconsin -- La Crosse -- Mental health